Lean Manufacturing Implementations for Process Improvement in a Company Operating in FMCG Sector - Emir, Oğuz; Karataş, Samet; Ay, Eren; Özker, Hümra; Gergin, Zeynep (Springer, Cham, 2018)
In order to survive in the global contest, enterprises have to increase their productivity via better use of their production resources. Hence, companies increasingly implementing lean management principles, which help them generate value and satisfy the requirements of their customers, through the elimination of non-value adding activities and pursuing continuous improvement in the processes. This study is an example of a process improvement that is applied to one of the fmcg company in Turkey. The project is implemented in packaging lines of Perfetti Van Melle Turkey, which is a global company, engaged in confectionery production and distribution, operating in more than 150 countries. The Turkey plant has been implementing various waste reduction practices for three years, and this project has been initiated to support the design of the packaging zone of the production system, considering the total seven wastes of lean management; namely overproduction, overprocessing, inventory, defects, transportation, motion, and waiting. It is desired to improve the performance of the packaging lines in order to keep up with the growing competition and fulfil the rapidly rising demands. The study begins by observing processes of packaging lines. The scope is determined by examining utilization rates, general line efficiency (GLE) and operational efficiency (OE). Then, selected lines are analyzed using value stream mapping (VSM) for waste identification, and statistical process control methods are implemented for improvements. The main objective is to increase the line efficiency rates that are calculated based on production quantities and scheduled time parameters. Improvement opportunities are proposed with future state VSMs by utilizing appropriate lean manufacturing techniques. Furthermore, a simulation study using ARENA Software is performed to evaluate proposed enhancements and to compare the alternative implementation scenarios.
Keywords: Lean production; Value stream mapping; Fast moving consumer goods; Simulation; Packaging